The relationship between achievement motivation, learning strategies and performance in the professional training of young athletes - Xin, S.; Han, D.; Feng, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Athletes often feel confused in the early stages of professional training. Nevertheless this period is essential in developing the fundamentals of professional training. As such, it is important to seek a reasonable way to assist athletes overcome the psychological issues which may arise. This paper emphasizes the relationships between motivation strategies and achievement during the early training period. Methods Athletes from 5 different majors in competitive sports schools were recruited for this study. A number of theories were used including the reason-summary theory, the achievement-goal theory and the selfefficacy principle. The research methods used included a literature review, psychological measurement and statistical analysis. The purpose is to summarize the relationship between motivation, strategies and achievement in different stages during one year of professional training. Results / Discussion Expectation and performance were largely influenced by each other both in the initial and final periods of the year. This shows that expectation affects results. Self- value cognition had little effect on performance in the early period, but in contrast, there was a strong relationship between the two areas later in the year. This shows that self-value cognition can influence performance. It was difficult to apply cognition strategies early in the year, and they were more easily employed in the later stage of the year. In conclusion, relationships do exist between motivation, strategies and achievement.